JENIS DAN KEPADATAN TIKUS DI PANTI ASUHAN “X” KOTA SEMARANG - Rani Kristiana Putriosa Saragih; Martini Martini; Udi Tarwatjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Mice are wild animals that are often associated with human life. The high rat population can have an impact on various areas of human life. Mice can also transmit several other diseases including murine typhus, leptospirosis, salmonellosis, richettsial pox, rabies, and trichinosis. This study was conducted to determine the type and density of mice, ectoparasites found in mice, sanitation and clean behavior patterns in orphanages